2018
DOI: 10.5559/di.27.4.04
|View full text |Cite
|
Sign up to set email alerts
|

National Innovation System: Where do Government and Business Diverge?

Abstract: The paper investigates the national innovation system and divergences in the prioritisation of key measures of the national institutional framework linked to the policy mix supply side. Two acting populations from the Republic of Croatia were selected for this process: on one side, 33 governmental representatives of the institutional framework (IF) ecosystem, and the "opposite side" of 93 owners or CEOs of firms as policy targets or beneficiaries. The produced results were additionally verified through 18 semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(30 reference statements)
0
1
0
2
Order By: Relevance
“…In order for businesses to fully exploit the potential of e-government, and not just use the services provided by law as mandatory, it is necessary for the Government to promote existing e-services as well as the benefits of using them. More broadly, the implementation of innovation policy, and the support of the Government in this context, is one of the important factors for successful digitization of public services [41]. The results of the research have indicated that information literacy is not a limiting factor in the use of electronic services.…”
Section: Discussionmentioning
confidence: 98%
“…In order for businesses to fully exploit the potential of e-government, and not just use the services provided by law as mandatory, it is necessary for the Government to promote existing e-services as well as the benefits of using them. More broadly, the implementation of innovation policy, and the support of the Government in this context, is one of the important factors for successful digitization of public services [41]. The results of the research have indicated that information literacy is not a limiting factor in the use of electronic services.…”
Section: Discussionmentioning
confidence: 98%
“…Internet se koristi kao otvoren i svima dostupan medij, podržan novim tehnologijama, a na kojemu pre- 20 vladava temeljno načelo gospodarskog interesa. 27 Uočeno je da su semiotika te informacijske i komunikacijske znanosti u koherentnom odnosu.…”
Section: Pregled Literatureunclassified
“…Pri analizi znakovlja bit će obrađeni strani i domaći proizvodi, ukazat će se na elemente koji proizvode čine prepoznatljivima, te će se naglasiti značaj kvalitetno odabranog 27 Castells, M. (2013.…”
Section: Ciljevi Istraživanjaunclassified